(Ba0.6Sr0.4)TiO3/PEEK composites modified by polyethersulfone with low dielectric constant and high dielectric tunability under DC bias. (1st March 2023) - Liu, Shuhang; Guo, Yiting; Hu, Guoxin; Wu, Sichen; Xu, Jie; Chen, Jianxin; Bulejak, Weronika; Baxter, Harry; Yang, Bin; Kong, Jie; Szafran, Mikołaj; Gao, Feng
Abstract: Ceramic/polyetheretherketone (PEEK) composites show a wide range of applications and have attracted extensive interest in the scientific community due to their outstanding dielectric and mechanical characteristics. However, the interface connection between the ceramic and PEEK is a vital issue that must be addressed to improve their physical and electrical properties. In this work, the polyethersulfone resin (PES) was selected as interface modifier between barium strontium titanate (Ba0.6 Sr0.4 TiO3, BST) and PEEK. Cold-pressing sintering was used to create BST/PEEK materials with superior dielectric frequency stability and dielectric tunability. The effects of PES content on the morphology and dielectric characteristics of PES modified BST/PEEK materials were investigated. The results showed PES could improve the dispersion of BST particles in polymer. The dielectric constant, dielectric tunability, and breakdown strength increased first, then reduced as PES content increased. The composite had the most homogeneous microstructure and the best dielectric properties when the PES content was 7.5 vol%. The frequency dispersion factor F (x) was much smaller than that of other ceramic/polymer composites reported. In addition, the dielectric tunability of the composites could reach a relatively high level (34.18%) while the dielectric constant was as low as 14. The dielectric tunable efficiency ( T uE ) was proposed to evaluate the property of low dielectric constant and high dielectric tunability under DC bias. The T uE of PES modified BST/PEEK composites show the highest value comparing with reported dielectric tunable composites. This research laid the path for the development of a novel ceramic/polymer composite with good interface bonding and high dielectric tunability. Graphical abstract: The structure of a material plays a decisive role in its properties. We obtained PES-BST/PEEK composites with higher dielectric properties by improving the interfacial bonding of ceramic and polymer phases in the composites. The high dielectric tunability with low dielectric constant of the PES-BST/PEEK composites is beneficial to the engineering applications of composite materials in integrated circuits and microwave dielectric devices. Image 1